Reproductive seasonality and environmental effects in green turtle (Chelonia mydas) nesting at Penang Island, Malaysia - Mohd-Salleh, Sarahaizad; Nishizawa, Hideaki; Mohd Sah, Shahrul Anuar; Khan Chowdhury, Ahmed Jalal (Cambridge University Press, 2020)
For species with environmental sex determination, understanding the relationship between reproduction and environmental factors is important for predicting their reproductive output. Here, we study intra-annual variation in green turtle nesting during the 2010-2016 seasons at Penang Island (5°16′28″-5°28′15″N 100°10′52″-100°11′55″E), Malaysia. The additive modelling on a monthly-basis number of nests shows that fluctuation in the number of nests relates to temperature in addition to month of year, rather than precipitation. The number of nests tended to be higher in response to higher temperature during March-July, whereas the lower temperature during August-February also tended to result in a relatively higher number of nests. Concentration of nests during March-July resulted from a shorter inter-nesting interval during warm temperatures, whereas relatively low temperatures may homogenize the temporal distribution of the number of nests. This study provides fundamental information for green turtle nesting seasonality in response to environmental change.